BAD BUGS NO DRUGS-A REVIEW ON NDM-I - MR. M. SENTHIL KUMAR; MR. J. BALASUBRAMANIAN; MS. GARGEYI PAVULURI; MS. HAREESHA CHAMARTHI; MS MADHURI.K. (International Journal of Pharma and Bio Sciences, 2011)
A dangerous new mutation that makes some bacteria resistant to almost all antibiotics has become increasingly common throughout the world. Experts in antibiotic resistance called the gene mutation, named NDM-1(New Delhi Metallo-beta-lactamase), “worrying” and “ominous” and they feared it would spread globally. The spreading of this is increasing day by day. So, the scarcity of the antibiotics and the need of these in the present condition show the target to the world. The potential of NDM-1 to be a worldwide public health problem is great, and co-ordinated international surveillance is needed.